Design- and Craft thinking analysed as Embodied Cognition - Groth, Camilla (FormAkademisk, 2016)
Through the concept of design thinking the act of designing is presented as an intellectual activity, and the act of planning the design is elevated over the making process. However, the importance of materiality and the embodied sense-making that occurs in this context should not be forgotten. In this study, embodied cognition in design and craft practices was investigated through three case studies. The study takes on an enhanced tactile perspective as a methodological platform; thus, the cases involve 1) deafblind makers in ceramics, 2) a practice-led self-study report on tactile experiences while working with clay and 3) a study on design students’ use of their tactile sense during material exploration. The results show that the act of thinking design involves the body as a knowledge provider.